2019
DOI: 10.1177/0954405419863221
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the chip morphology, tool–chip contact length, workpiece vibration, and surface roughness during high-speed face milling of A6061 aluminum alloy

Abstract: In this study, experiments of high-speed face milling of A6061 aluminum alloy with a carbide insert milling cutter under dry cutting conditions were conducted. The contact length between tool and chip, the workpiece vibration amplitude, and the arithmetic average surface roughness were measured under varying cutting conditions (cutting speed, feed rate, and depth of cut). The characteristics of chip morphology were observed using scanning electron microscope. Experimental results showed that the increasing cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…In actual cutting, processing efficiency, cutting power, tool wear, workpiece surface integrity and other performance need to be considered comprehensively [49,50]. High cutting temperature is the main cause of tool wear, resulting in machined surface having residual stress and other defects [51,52].…”
Section: Fundamentals Of Forward-and-reverse Multidirectional Cuttingmentioning
confidence: 99%
“…In actual cutting, processing efficiency, cutting power, tool wear, workpiece surface integrity and other performance need to be considered comprehensively [49,50]. High cutting temperature is the main cause of tool wear, resulting in machined surface having residual stress and other defects [51,52].…”
Section: Fundamentals Of Forward-and-reverse Multidirectional Cuttingmentioning
confidence: 99%
“…where g is a positive constant. l i , b, and c are the parameters to be determined, respectively, which are obtained by equations (17) and (18) in the matrix form…”
Section: Radial Basis Function Modelmentioning
confidence: 99%
“…Additionally, Baowan et al 16 revealed that the surface roughness and tool life were significantly influenced by the cutting angle and tools. Pham et al 17 stated that the tool-chip contact length, the workpiece vibration, and the surface roughness were increased with F o r P e e r R e v i e w 4 increasing cutting depth and feed rate for the dry milling of A6061 aluminum alloy. Jahan et al 18 concluded that the mid-level of the feed and depth of cut could be used to decrease the tool wear and surface roughness in the milling of polycarbonates.…”
Section: Introductionmentioning
confidence: 99%
“…Grain refining, decreasing the number of blowholes, heat-affected zone (HAZ) morphology modification, and reducing residual stresses are advantages that lead to improving mechanical properties in the weld zone [1]. The vibrations in the manufacturing processes are imparted on the tool [2][3][4][5][6] and workpiece [7][8][9][10] that correspond to the electrode and weld-pool vibration in welding. The vibration of the arc due to pulsed current also leads to agitation in the weld pool.…”
Section: Introductionmentioning
confidence: 99%